COMMUNITY KNOWLEDGE, ATTITUDES, AND BEHAVIOR TOWARDS SOCIAL DISTANCING POLICY AS PREVENTION TRANSMISSION OF COVID-19 IN INDONESIA - Budi Yanti; Eko Mulyadi; Wahiduddin Wahiduddin; Revi Gama Hatta Novika; Natalia Sri Martani; Nawan Nawan; Yuliana Mahdiyah Da'at Arina (Indonesian Journal of Health Administration (Jurnal Administrasi Kesehatan Indonesia), 2020)
Background: Coronavirus Disease 2019 (COVID-19) caused by SARS-CoV2 recently became a pandemic worldwide, such as in Indonesia. Social distancing is one of the recommended mitigations to reduce the risk of disasters, such as morbidity and mortality caused by COVID-19. Community compliance with social distancing is a part of the pandemic control.Aims: This study identified knowledge, attitudes, and behavior towards the prevention of SARS-CoV-2 transmission through social distancing during COVID-19 pandemic among Indonesian community.Methods: This descriptive study applied a cross-sectional design and distributed closed questions with online  questionnaire randomly to 34 provinces in Indonesia on social media networks and e-mail. This study successfully collected 1,102 respondents from 29 provinces in Indonesia. The data were analyzed descriptively by calculating frequency, percentage, and cross-tabulation.Results: This study had successfully identified  99%, 59%, and 93% of respondents with good knowledge, positive attitudes, and good behavior respectively towards  social distancing. Among the respondents who had good knowledge showed positive attitudes (58.85%) and good behavior (93.3%). The respondents who had positive attitudes showed good behavior (96.7%).Conclusion: Indonesian community had good knowledge, attitude and behavior towards social distancing as a way to prevent the virus transmission. This strongly supports disaster mitigation in controlling the COVID-19 pandemic in Indonesia. Keywords: attitudes, behavior, COVID-19, knowledge, social distancing.